(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
At different times, society has created an opportunity for its members to form a respectful attitude to work, to change the feeling of alienation from it, to spend their labor from childhood, to independently determine the forms of identification. However, it did not always go as planned. In sociological research, from adolescence and adolescence, the profession is chosen by those around them (in relation to parents, acquaintances, influential people, etc.) in order to achieve the "maturity" of the person. According to folk proverbs, "a young man has less than forty trades." But it must be admitted that such proverbs are losing their significance in an informed society. Instead, the term "narrow specialization" became more common. It is directly related to ability.